Edukasi Pembelajaran Pendidikan Agama Islam Berbasis Nilai Karakter - Irna Nur Solikah; Muhammad Syauqi Mubarok (PT Cendekia Education Center, 2026)
This community service activity aims to strengthen Islamic Religious Education (IRE) learning through the integration of character values. The program was implemented using an educative–participatory approach that actively involved participants in discussions, simulations, and reflective activities. The stages of the activity included preparation, implementation, and evaluation, focusing on character values such as religiosity, honesty, responsibility, discipline, tolerance, and social awareness. Data were collected through observation, questionnaires, and focused group discussions to examine changes in participants’ understanding and attitudes after the program. The results indicate an improvement in participants’ comprehension of character-based IRE learning and an increased awareness of the importance of applying Islamic values in daily life. Participants were also able to identify practical strategies for integrating character values into IRE learning contexts. This activity demonstrates that character-based Islamic Religious Education can be effectively strengthened through community-based educational programs. Therefore, continuous and collaborative efforts involving educators, families, and communities are essential to ensure the sustainability of character education rooted in Islamic values. Keywords: Islamic Religious Education, character education, community service, moral values, participatory learning.